PREGNANT MARES SERUM GONADOTROPHIN INCREASES NUMBER OF EGGS AND ACCELERATES LAYING PERIOD OF BALI DUCK WITH DELAYED EGG PRODUCTION - Kota Budiasa, Made; Bebas, Wayan (Jurnal Veteriner, 2008)
A study was carried out to determine the effect of Pregnant Mares Serum Gonadotrophin (PMSG) on the weigth of ovary, the number of developing follicles and the onset egg production in ducks with delayed egg production. In this study, as many as 40 Bali ducks were used and they were divided into 4 groups in a completelty randomized design i.e. control group (TO) treated with NaCl 0,9%, group T1 treated with PMSG dose 5 IU per duck, group T2 treated with PMSG dose 10 IU per ducks and group T3 treated with PMSG dose 20 IU per duck intramuscularly. The weight of ovary increased significantly with the increasing dose of PMSG, i.e dose 0 IU (21,04 + 3,90 gram), dose 5 IU (25,40 + 5,31 gram), dose 10 IU (49,52 + 5,05 gram) and dose 20 IU (59,30 + 4,66 gram). The number of developing folilicles also increased significantly with the increasing dose of PMSG, i.e dose 0 IU (1,4 + 0,5 follicles), dose 5 IU (2,4 + 1,34 follicles), dose 10 IU (5,8+2,07 follicles) and dose 20 IU (8,6+1,67 follicles). In addition, the onset of egg production was shortened significantly with the increasing dose of PMSG, i.e. dose 0 IU (19,0+1,58 days), dose 5 IU (16,8+1,3 days), dose 10 IU (14,2+1,92 days) and dose 20 IU (9,6+14 days). PMSG treatment was proven to increase the egg production capability of ducks with delayed egg production.
Keywords: PMSG, Bali duck, early prodution, ovarium weigh, follicle growth